Well, you must have made some mistakes when computing the normal form since it is incorrect. Here is how the computation is done for the first formula by a step-by-step Shannon decomposition on the variables d,c,b,a:

a&!b&!c&!d | c&!a&!d | d&!a
= (d ? !a
: a&!b&!c | c&!a )
= (d ? !a
: (c ? !a
: a&!b ))
= (d ? !a
: (c ? !a
: a&!b ))
= (d ? !a
: (c ? !a
: (b ? false
: a )))
= (d ? (a ? false
: true)
: (c ? (a ? false
: true)
: (b ? false
: (a ? true
: false))))

This is what the tool computed, and it can also be read from the corresponding BDD using the same variable ordering:

The same way, you can compute the SNF for the other formula.